Aplicação e beneficios da metodologia ativa (ABP) em disciplina gamificada de uma Pós-Graduação em Engenharia de Produção - Ribeiro, Alexandro Luis do Nascimento (Universidade do Vale do Rio dos Sinos, 2016)
The social changes generated by technological innovations, require a new professional profile of students from the engineering courses, skills as a more collaborative attitude, innovative and creative are desired profiles by companies and encourage reflection on the learning methods used by postgraduate course in engineering. The purpose of this article is to deepen the knowledge of the active learning methodology with focusing problem-based learning (PBL) and present an analysis of its benefits in gamified discipline of postgraduate course in Production Engineering. The study of structured case in descriptive research into the classroom during the discipline of Lean Manufacturing System (LMS) aims to evaluate the benefits of these methods in the students formation. With the gamified discipline, prepared to insert learning contents after a building game troubleshooting that simulates an industrial production process, the students could have the experience of living the difficulties of introducing the LMS. In the other hand, students could interact, experience group troubleshooting and change knowledge and experiences with facilitator. There was a great adherence to the LMS contents by the students, along with the satisfaction in participate of a real learning activity.
Keywords: Metodologia de aprendizagem ativa; Gamificação; Aprendizagem baseada em problemas (ABP); Sistemas enxutos de produção; Active learning methodology; Gamification; Problem-based learning (PBL); Lean manufacturing system; Postgraduate course in production engineering